Simulation program for 4th axis CNC machining in NX CAM system - Mohamad, M. H.; M. Nafis, O. Z. (Universiti Malaysia Pahang, 2019)
This paper presents the development of a simulation program to improve the process planning and simulation for 4th axis machining in NX CAM systems. A customised graphical user interface (GUI) was developed to enhance the simulation process planning and reduce the dependency on the user’s experience while developing the machining program in NX CAM systems. The simulation operation was recorded using a journaling tool available in NX CAM while visual basic programming was utilised to customise the code. The results indicate that the developed programs are capable of optimising the 4th axis machining simulation by reducing the processing steps and time with minimum process planning tasks.